Pemaknaan Kesejahteraan pada Dosen Perguruan Tinggi Islam Berdasarkan Perspektif Psikologi dan Islam - Eneng Nurlaili Wangi (Jurnal Psikologi Islam dan Budaya, 2022)
Working at certain times sometimes drained the mind and physical condition. Also, work situations that are not appreciative can affect their work well-being. The concept of well-being in Western and Islamic are both aim to fulfill enjoyment. However, well-being in an Islamic perspective is based on faith and piety and the goal of the afterlife. This study aims to describe work well-being which is based on faith and devotion at work. This research used qualitative method with a descriptive phenomenological approach, through interviews and observation methods. Participants were 2 lecturers of Islamic Higher Education (PTI) in the city of Bandung. The results of the study show that respondents have five aspects of well-being, that are positive emotions, involvement, relationships, meaning, and achievements which are motivated by strong faith.